Development of an augmented reality-assisted e-module on the virus topic to improve students' conceptual understanding and learning independence - Mauludin, Nurman; Ismaniati, Christina; Rassyi, Sultan Fakhrur (Assimilation: Indonesian Journal of Biology Education, 2025)
The research and development aims to produce learning resources in the form of augmented reality-assisted e-modules on virus materials that are: (1) suitable for use, (2) practical, and (3) effective for improving material understanding and learning independence of high school grade X students. This type of research was research and development, using the development model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The data analysis technique used was the MANOVA test with a significance level of 0.05. The results of this research and development are the product of an assisted e-module learning resource augmented reality on virus material for high school class X, with the following results: (1) feasible based on the results of the validity test by material experts, media experts, and trials with students, (2) effective based on material understanding test data, and student learning independence questionnaire, and (3) practical based on practicality questionnaire data. The data from the test results obtained a significance value of 0.013. This value shows the value obtained 0.05. Therefore, it can be stated that there is a significant influence of the use of assisted e-modules augmented reality on viral material to increase material understanding and student learning independence.